Characterization of Titanium Films Deposited with a Cathodic Arc Using a Straight Magnetic Duct - Bermeo, Diego Fernando (2014)
Nanostructured Ti films were obtained employing a cathodic arc with a straightmagnetic filter. The films were characterized using X-ray diffraction, scanning electron andatomic force microscopy. The films were found to be dense and with columnar grains,whose size increased with the exposure time. The number of macroparticles, the filmroughness and the deposition rate were also analyzed, and the latter compared with theresults of a fluid plasma model. Number of macroparticles and film roughness in sampleslocated ahead of the magnetic duct inlet were higher than those determined fromsamples placed inside the magnetic duct. The deposition rate depended on the axial andradial position inside the duct. The thickness along the radial position was more uniformfor samples located at axial positions near the filter extremes, but the mean depositionrate was lower at these positions. Measured and modeled deposition rates agreed reasonablywell.